Promoting Students’ Interest, Enjoyment, and Social Interaction During Vacant School Hours through Rally Games - Dispo, Raynalie; Macaraeg, Danilo Jr.; Beled, Wennielyn; Buhay, Jimford; Garma, Michael Francis (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the preferences, key features, and perceived benefits of rally games among Grade 10 students during vacant school hours at Kings College of the Philippines–Bambang Inc. The study was conceptually anchored on the premise that enjoyment, social interaction, teamwork, and participation influence student engagement in physical activities. Using a descriptive-correlational research design and descriptive survey method, data were collected from 70 Grade 10 students selected through purposive sampling. A structured, self-administered questionnaire developed by the researchers and validated through expert review was used to assess students’ preferred rally games, perceptions of game features, and perceived benefits of participation. Data were analyzed using frequency counts, percentages, means, and standard deviations. Findings revealed that badminton was the most preferred rally game, followed by volleyball and basketball. Students generally perceived competition as a motivating factor that enhanced engagement, focus, skill development, and achievement. Rally games were also viewed as enjoyable, accessible, and easy to play, contributing to increased interest in physical activities, positive emotional experiences, and stronger peer interaction. Respondents reported that participation in rally games promoted teamwork, cooperation, friendship-building, and social connectedness. Overall, the results indicate that rally games positively influence students’ interest, enjoyment, motivation, and social interaction during vacant school hours. The study concludes that rally games are effective student-centered activities that support the physical, social, and emotional well-being of learners. It recommends the implementation of structured yet enjoyable rally game programs that emphasize teamwork, positive competition, accessibility, and inclusive participation. The study supports Sustainable Development Goal (SDG) 3: Good Health and Well-Being by encouraging physical activity and promoting psychological well-being among adolescents. It also supports SDG 4: Quality Education by fostering student engagement, social development, and meaningful use of school time. The sustainability impact of the study lies in its contribution to healthier school environments, increased student participation, and stronger peer relationships. The findings may assist educators in developing sustainable school-based physical activity programs that promote holistic student development and positive school communities.
Keywords: Badminton; Competition; Enjoyment; Interest in Physical Activities; Physical Activity; Rally Games; Social Interaction; Student Engagement; Teamwork; Vacant School Hours